O conceito de consciência social na tese de Sinequismo de Charles S. Peirce - Zuliani, Maria Conceição (2011)
The theme of this dissertation is the concept of social consciousness in the philosophy of the North American thinker Charles Sanders Peirce (1839-1914). We propose in this work to make a cut, through the study of various writings of Peirce and the experts of his work, which leads us to a concept of social consciousness. We assume, as justification for this research, to make a contribution and the translation to Portuguese of the text Immortality in the Light of Synechism, through a selection of articles translated and commented, contemplating the development ontological, logical and phenomenological of his doctrine of continuity and semiotics